ANALISIS PENGENDALIAN PERSEDIAAN TEPUNG TERIGU DI UMKM CITRA MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN JUST IN TIME (JIT) - Afni Khadijah; Freshky Galatia Lada; Achmad Syarifudin; Nur Hidayanti (Prodi Teknik Industri, Fakultas Teknik, 2023)
As a Micro, Small and Medium Enterprise that is engaged in the food business, namely crackers, the raw material used in Citra UMKM is wheat flour which is the main raw material in making crackers. raw material. In this study, the authors review controls to determine the size of the safety stock. the availability of raw materials for Citra UMKM by comparing the two availability systems. This study aims to determine the amount of safety stock and when to reorder and compare the availability control system that has been carried out by Citra UMKM using two availability control systems, namely the Economic Order Quantity (EOQ) method and the Just In Time (JIT) method. After further analysis showed that in controlling the inventory of raw materials, the costs incurred by Citra UMKM were greater than those using the Economic Order Quantity (EOQ) method and the Just In Time (JIT) approach. Meanwhile, if the Economic Order Quantity (EOQ) approach is compared with Just In Time (JIT) with each of the total inventory costs between companies, EOQ and JIT are IDR 10,000,000, IDR 1,109,995 and IDR 934,924, using the JIT approach is superior because the number of higher orders and lower total inventory costs.